Relationships Education Level of Parents With Kids Healthy Lifestyle - Kartikasari, Galuh (STAI Miftahul Ula Nganjuk, 2016)
This article is about a research Aimed at finding out the correlation between parents educational level and elementary school childrens pattern of healthy living in Depok, Sleman, Yogyakarta. The research population consisted of 1,600 parents of 5th grade students from 56 state elementary schools in Depok, Sleman, Yogyakarta (DIY). As the research sample, 300 parents from nine public elementary schools were selected by using proportional random sampling. The result of a descriptive analysis reveals that 86.3% of elementary school childrens pattern of healthy living in Depok, Sleman, Yogyakarta is Categorized good and 42.7% of Reviews their fathers and 38.3% of Reviews their mothers are senior high school graduates. The result of a correlation analysis reveals a significant correlation between parents educational level and state elementary school childrens pattern of healthy living in Depok, Sleman, Yogyakarta.